Teacher assessment literacy: a systematic review - Pastore, Serafina (Frontiers in Education, 2023)
Teacher assessment literacy, generally defined as a set of knowledge and skills a teacher needs to effectively enact assessment in classroom, has been a priority in the educational policy and educational research agenda for decades. For a long time, it has been identified with standardized measurement and classroom testing. The interest on this topic is related not only to the accountability pressures and to the identification of assessment as a lever for school and system reform, but also to the need for teachers to support student learning by developing and implementing responsive assessments within their classrooms. Considerable efforts have been made to prepare novice and expert teachers in understanding how to deal with aspects of assessment practice and how to use the assessment results. Although the research on teacher assessment literacy is quite wide, it continues to demonstrate how teachers struggle with assessment, especially when they are required to transfer new approaches and theories into the actual classroom context. This systematic review synthetizes the literature on teacher assessment literacy considering how it has been defined and studied over the last 10 years (2013-2022). Documenting and comparing the different expressions and definitions of assessment literacy used in the 42 selected studies, this systematic review offers a detailed overview of the changes occurred in the conceptualizations of assessment literacy. Along with the analysis of the theoretical/conceptual frameworks and research methods used to investigate teacher assessment literacy, the scrutiny of its foundational components represents a useful base to orient pre- and in-service teacher education. On the backdrop of strengths and weaknesses of this review, research priorities and practical implications of the findings are discussed.